Medical Students’ Frequency of Playing Online Games with Their Academic Performance: A Cross-Sectional Study - Hayati, Nur; Roesdiana, Novada Indra (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2025)
Background: Recently, internet users in Indonesia are getting higher. About 10% of these users are online gamers. Playing games on video or computer is believed to be educationally beneficial, but this is still limited to educational type games for learning activities. This study aims to determine the relationship between the frequency of playing commercial online games on smartphones with academic achievement of the Medical Faculty of Universitas Muhammadiyah Yogyakarta students.Methods: This was a quantitative study with cross-sectional research design. Data on the frequency of playing online games on smartphones, and academic achievements were taken using a questionnaire. Data analysis used Spearman's correlation test to find out the correlation between the frequency of playing online games on smartphones with academic achievement.Results: The frequency of playing online games on smartphones gets results with category: non-gamers 46.6%, infrequent gamers 24.3%, regular gamers 17.4%, and frequent gamers 11.7%. There is a negative relationship between the frequency of playing online games with academic achievement with a p value of 0.002.Conclusion: The frequency of playing online games on smartphones is negatively correlated with the academic achievements of students of the Medical Faculty of Universitas Muhammadiyah Yogyakarta.